Consumer Health Informatics Informing Consumers and Improving Health Care - Lewis, Deborah; Eysenbach, Gunther; Kukafka, Rita; Stavri, P. Zoe; Jimison, Holly (Health Informatics, 2005)
Edited by five leaders in the field of health informatics, Consumer Health Informatics explores all aspects of this evolving science. This comprehensive volume will be an indispensable tool for both professionals and students as it details the broad scope of consumer health informatics and its impact on today's progressive and ever-changing world of health care. The inclusion of several case studies serves to examine pertinent topics, namely computer-based information for cancer; National Library of Medicine initiatives; and web-based patient preferences and utilities. Designed for use by medical IT specialists, physicians, nurses, healthcare providers, and professors and students of medical informatics, the book's chapter highlights include patient empowerment; frameworks and models for health behavior change and patient education; patient to patient communication; patient to provider communication; privacy and confidentiality; ethical issues; evaluation methods, and more.